Impact of Functional Groups on the Copper-Initiated N-Arylation of 5-Functionalized Pyrrolidin-2-ones and Their Vinylogues - Baudelet, Davy; Daïch, Adam; Rigo, Benoît; Lipka, Emmanuelle; Gautret, Philippe; Homerin, Germain; Claverie, Christelle; Rousseau, Jolanta; Abuhaie, Cristina-Maria; Ghinet, Alina (Synthesis, 2016)
The electronic effects governing the N-arylation of pyrrolidone were investigated. The generalization of our preliminary findings on a copper(I)-catalyzed Csp2-N coupling process was first improved with a wide variety of aryl and heteroaryl halides and methyl pyroglutamate. The optimized protocol was further extended to pyrrolidin-2-ones substituted at the C5-position with an aryl group bearing an electron-donating or electron-withdrawing group as well as to some of their substituted enaminoester vinylogues. The impact of substituents at the N- and C5-position on these coupling processes seemed to be pivotal for determining both the reaction profiles and yields.
Keywords: arylation; heterogeneous catalysis; copper; cross-coupling; lactams; heterocycles